2022
DOI: 10.3390/ijerph19053063
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to Health Efficiency across the European Space through the Lens of the Health Budget Effort

Abstract: In the context of the COVID-19 pandemic, financial resources allocated to the health system have been refocused according to priority 0: fighting the pandemic. The main objective of this research is to identify the vulnerabilities affecting the health budget effort in the EU and in the Member States during the health crisis period. The analysis takes into account relevant statistical indicators both in terms of financial allocation to health and expenditure on health protection of the population in the Member … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…The results obtained from structural equation modeling support hypothesis H1. According to the research findings, we identified a significant positive correlation between healthcare expenditures and health status, confirming previous research conclusions (1,28,43,56,57) about the importance of healthcare investments in promoting a healthy population and societal well-being. We found a significant positive influence of social protection expenditures on health status mediated through healthcare expenditure.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The results obtained from structural equation modeling support hypothesis H1. According to the research findings, we identified a significant positive correlation between healthcare expenditures and health status, confirming previous research conclusions (1,28,43,56,57) about the importance of healthcare investments in promoting a healthy population and societal well-being. We found a significant positive influence of social protection expenditures on health status mediated through healthcare expenditure.…”
Section: Discussionsupporting
confidence: 88%
“…Academic literature ( 1 , 6 ) signals financial allocations for healthcare and social protection services imbalances. Social protection must include easy and free access to healthcare services for vulnerable populations exposed to poverty and aging to promote equitable healthcare access.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation